Statistical analysis of student's life satisfaction at higher learning institution / Norafefah Mohamad Sobri ... [et al.] - Mohamad Sobri, Norafefah; Ismail, Nor Azima; Wan Yaacob, Wan Faizah; Nordin, Noor Ilanie; Wan Mokhtar, Wan Mohd Zawir; Muhamad Yusuf, Muhammad Nur Aidil Ariff; Abdullah Zawawi, Muhamad Akmal (Faculty of Computer and Mathematical Sciences, Universiti Teknologi MARA Cawangan Kelantan, 2022)
Life satisfaction is one of the important aspects of life for students since it is part of their daily life. Due to the decreasing life satisfaction among students, this study was carried out with the intention to find out the determinants of students' life satisfaction at higher institution. There are several factors investigated in the study including stress, academic performance, peer's relation and financial status. Stratified random sampling method was implemented to select 298 students in UiTM Kota Bharu as respondents in this study. Demographic analysis used to analyze the socio-demographic data. Pearson's correlation coefficient was utilized to analyze the significant relationship between students' life satisfaction and independent variables; namely stress, academic performance, peer's relation and financial status. The result shows that all the independent variables are significantly have relationship between the life satisfaction. Independent t-test was carried out to analyze the significant different of students' life satisfaction between gender. It can be concluded that there is no significant different between gender (male and female) and life satisfaction. Multiple linear regression method was applied to determine the significant factors that influence students' life satisfaction. As a result, the four factors turned out to have a significant effect towards students' life satisfaction.